Infrastructure Health Monitoring System (SHM) Development, a Necessity for Maintance and Investigation - Priyo Suprobo; . Faimun; Arie Febry (International Conference on Engineering and Technology Development (ICETD), 2013)
Failure of Kutai Bridge already give Indonesia civil engineer a blow in face. The failure which bring cause human accident make a new challenge to Indonesia civil engineer not to wait till failure but to safe before the construction failure. By the development in sensor and monitoring technology the idea become more realistic. Structure Healthy Monitoring (SHM) become new idea to detect, to monitor and to find out the reliability of structure. The development and research in Indonesia for SHM till now are presented and compared to other country. SHM research are need to predict behaviour of bridge by using data from monitoring to gain healthy condition.